PENGARUH METODE PEMBELAJARAN DAN BERPIKIR KREATIF TERHADAP HASIL BELAJAR SEJARAH SISWA SMA - KUSUMA, SUMARDIANSYAH PERDANA (Program Studi Pendidikan Sejarah Pascasarjana Universitas Negeri Jakarta, 2014)
This research aims to investigate the impact of learning methods and creative thinking skills toward history learning outcome of students at Al-Azhar Kelapa Gading Islamic Senior High School. The method used in this research is experimental research method with the treatment design by level 2 x 2. The instrumen used to assess students creative thinkingâs skills is in quesionnaire form, while the instrument used to assess students achievement is in the multiple choice form. The result show that: 1) history learning outcome of students using mind mapping learning methods are higher than those history learning outcomes of students using conventional learning methods, 2) there is interaction effect between learning method and creative thinking on history learning outcome of students, 3) history learning outcome of students who has high creative thinking and using mind mapping learning method are higher than students using the conventional learning method, 4) history learning outcome of students who has low creative thinking and using mind mapping method are lower than students using the conventional learning method.Keywords: learning methods, mind mapping, conventional, history learning outcomes, creative thinking